Arginine depletion as a therapeutic approach for patients with COVID-19 (2020)
The COVID-19 pandemic, caused by SARS-CoV-2, is a source of significant morbidity and mortality worldwide, and effective treatments are urgently needed. Clinical trials have largely focused on direct anti-viral therapies or on immunomodulation in patients with severe manifestations of COVID-19. One therapeutic approach that remains to be clinically investigated is disruption of the host-virus relationship through amino acid restriction, a strategy utilized successfully in the setting of cancer treatment. Arginine is an amino acid that has been shown in non-clinical studies to be essential in the life cycle of many viruses. As such, arginine depletion may represent an effective therapeutic approach against SARS-CoV-2. Several argininemetabolizing enzymes in clinical development may represent a viable approach to induce a low arginine environment to treat COVID-19 and other viruses. Herein, we explore the rationale for arginine depletion as a therapeutic approach for COVID-19.